Hvad er betydning? - Togeby, Ole (HERMES - Journal of Language and Communication in Business, 2002)
In the same way as Descartes defined body and soul, linguistic expression and meaning can be defined as extensive and divisible and as inextensive and indivisible respectively. Linguistic meaning is analysed in a model containing 1) the situation or scene of communication, 2) the physical utterance act, 3) the inextensive thought which is what the utterance counts as, and 4) the situation that the thought is a representation of. The thought is inextensive in time and space, but organized in a logical hierarchy of conceptual meaning included in propositional meaning, included in informational meaning, included in interactional meaning. Such a model of linguistic meaning makes it possible to make a functional analysis of, among other things, the overwhelming amount of monosemiation of the almost always polysemic lexemes of language.